The Enhancement of English Oral Production in an 11th Grade at Centro Formativo de Antioquia Through the Use of the Storytelling Strategy (2022)
ABSTRACT: This study is an action research project carried out with eleventh graders at Centro Formativo de Antioquia; a public institution located in El Centro, Medellín. The aim of this project was to enhance student oral production through the implementation of the storytelling strategy. The data collection method included two questionnaires, one at the beginning and the other one at the end of the implementation, two diagnostic activities, and observations registered in the student-teacher’s journal. Data were analyzed using the triangulation/comparison method with all the sources. The results showed that storytelling helps students to improve their speaking skills, that is to say their vocabulary, pronunciation, and fluency. Also, the findings showed that through the use of this tool students feel more motivated to participate in class in English and it also favors group interaction.